Differences in technical and tactical training of the world`s leading national teams in judo tournaments in 2017-2018 - Szczepanik, K.; Lech, G.; Witkowski, K.; Jaworski, J.; Palka, T.; Piepiora, P. (Archives of Budo, 2023)
Background and Study Aim: World-level judo athletes are characterized by a high level of technical-tactical skills. The purpose of this study was knowledge of the probable differences in the technical-tactical training of judo athletes of the Japanese, Georgian and French national teams.